Multilevel plasticity and altered glycosylation drive aggressiveness in hypoxic and glucose-deprived bladder cancer cells - Andreia Peixoto; Dylan Ferreira; Andreia Miranda; Marta Relvas-Santos; Rui Freitas; Tim S. Veth; Andreia Brandão; Eduardo Ferreira; Paula Paulo; Marta Cardoso; Cristiana Gaiteiro; Sofia Cotton; et al. (iScience)
Summary: Bladder tumors with aggressive characteristics often present microenvironmental niches marked by low oxygen levels (hypoxia) and limited glucose supply due to inadequate vascularization. The molecular mechanisms facilitating cellular adaptation to these stimuli remain largely elusive. Employing a multi-omics approach, we discovered that hypoxic and glucose-deprived cancer cells enter a quiescent state supported by mitophagy, fatty acid β-oxidation, and amino acid catabolism, concurrently enhancing their invasive capabilities. Reoxygenation and glucose restoration efficiently reversed cell quiescence without affecting cellular viability, highlighting significant molecular plasticity in adapting to microenvironmental challenges. Furthermore, cancer cells exhibited substantial perturbation of protein O-glycosylation, leading to simplified glycophenotypes with shorter glycosidic chains. Exploiting glycoengineered cell models, we established that immature glycosylation contributes to reduced cell proliferation and increased invasion. Our findings collectively indicate that hypoxia and glucose deprivation trigger cancer aggressiveness, reflecting an adaptive escape mechanism underpinned by altered metabolism and protein glycosylation, providing grounds for clinical intervention.